Política nacional de resíduos sólidos e a cidade sustentável: o plano de coleta seletiva do município de Salvador - COELHO, André Luiz Cardoso (2014)
A selective collection plan has been sued by BNDES and, in light of the National Solid Waste Policy (PNRS), has been prepared for the city of Salvador - here titled Salvador Selective Collection Plan (PCSS), the object of such a thesis. Cut the subject and the object, it has been proposed the following research problem: Through the local tax challenges by the National Policy on Solid Waste, the Waste Recycling Plan of Salvador discusses the necessary requirements to meet the challenges of restructuring this collection as a public policy? Such a thesis presents a critical analysis of this plan, using documentary analysis of the same, together with other legal plans and frameworks associated with it. A proper theoretical framework has been devised in order to support the axial node of such a study: the empirical and documentary research. The main constructs used departed from the founding authors, such as: the presentation of the City Theories of Freitag (2012); the critique of the distorted use of the concept of Ecology Park Urbana, (1976), is preferred to use the Urban Environment, developed from Howard (2002); the size of Environment and Natural Artificial through Santos (2008, 2009a, 2009b, 2012, 2013); and the Urban Environment and Sustainable Cities revisited, respectively, under the main lens about Leite and Awade (2012) as well as Souza (2010) - this seminal to the dimensions of urban planning instruments. In the economical institutional rationality analysis was necessary to understand the integration of institutional friction between justice and the economy according to Posner (2010), public choice Buchanan Jr. (1962, 1968, 1975.1985) and individual choice of North (1991, 2001, 2003, 2013). Interviews for the empirical part, have been applied with leading contemporary experts who have local executive action on the selective collection in order to investigate the possible shortcomings of the PCSS and at the same time, give details of institutional performance model of the same. A critical analysis succeeds the documentary research, the results of interviews and presentation and critique of PCSS, and then the results of the tested hypotheses are presented. The conclusion is that Salvador is not a sustainable city. The vast production of liquid and solid waste and urban expansion has aggravated such a problem. The PCSS has a sanitarian and distant view of PNRS. In addition, the document has been shy in its objectives and has low adherence to its formulation requirements. Essential levels of support or do not exist or are outdated and have not been considered in the formulation. The PCSS also needs to be integrated recycling and does not have a careful analysis of the production chain of recyclable and total logistics costs, concurrently is not explained methodologies and structured diagnostics. The model of selective collection needs to be assimilated by all, especially by the ruling class, but there is no maturity in the management of the treatment of municipal solid waste in Salvador, because there is a general lack of relevant legislation. An aggravating factor is that a significant part of policy makers have focused on the theme does not know in depth the national solid waste policy. The metric parameters have not been adopted, even partially. One of the outcomes of this study is to present a timeline of public policies of selective collection for the city and more explicit consolidated requirements for plan formulation of the PCSS nature. Therefore, the PCSS does not address the minimum requirements needed to meet the challenge of restructuring the selective collection as public policy and it is recommended that is not accepted as a tool for building a sustainable city.